Alan Paton's Cry, the beloved country - Bloom, Harold (Philadelphia : Chelsea House, 2004)
Examines different aspects of Paton's novel about race relations in South Africa, with a biographical sketch of the author and critical essays on this work.
Biographical sketch -- The story behind the story -- List of characters -- Summary and analysis -- Critical views -- Horton Davies on inspiration -- Sheridan Baker on the book as moral geography -- Edmund Fuller on tragedy -- Martin Tucker on the novel of forgiveness -- Myron Matlaw on stylistic understatement -- Robert L. Duncan on the suffering servant -- J.M. Coetzee on simple language -- Tony Adler on Cry, the beloved country and Lost in the stars -- Carol Iannone on Paton's tragic liberalism -- Mark Hestenes on Graham Greene and Alan Paton -- Works by Alan Paton.
Includes bibliographical references (p. 109-111) and index.
Keywords: Paton, Alan; Paton, Alan; Race relations in literature; Apartheid in literature; South African literature (English) -- History and criticism; South Africa -- In literature